ANALISIS PROSES EVALUASI KEBIJAKAN KABUPATEN/KOTA LAYAK ANAK (KLA) OLEH KEMENTERIAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK REPUBLIK INDONESIA - Rahmawati, Siti Sabrina; Azijah, Dewi Noor; Septiani, Athifah (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The existence of child protection in Indonesia still faces major challenges in harmonizing constitutional mandates with policy implementation at the regional level. Empirical evidence shows that although legal instruments are available, the synchronization of integrated child rights fulfillment systems is often hampered by bureaucratic complexity and cross-sectoral coordination. Although previous studies have extensively discussed Child Friendly District/City (KLA) policies, there is still a lack of analysis on policy evaluation mechanisms specifically carried out by central government units, particularly the Ministry of Women's Empowerment and Child Protection (KemenPPPA). This study seeks to explore the KLA policy evaluation process through a review of indicators of relevance, impact, effectiveness, efficiency, and productive economy at the Ministry of Women's Empowerment and Child Protection (KemenPPPA). Using a qualitative method based on field observations and in-depth interviews at the Deputy for Special Child Protection unit, this study explores the process from administrative verification to hybrid field verification (VLH). The findings show that the effectiveness of the 2025 KLA evaluation is highly dependent on the integration of quantitative and qualitative data on 24 indicators in 5 clusters of children's rights to ensure local government accountability. The implications of this research are expected to provide critical reflection for policymakers in strengthening a more adaptive and comprehensive child protection system.